On the dumping ground genus Scotaena Klug, 1810 (Hymenoptera: Tiphiidae: Thynninae): Phylogeny, taxonomy and geographic distribution - Carnimeo, Fernando Henrique; Noll, Fernando Barbosa (Zootaxa, 2018)
The Neotropical thynnine genus Scotaena is revised and a cladistic analysis is presented. The analysis, conducted from 75 morphological characters of 31 terminal taxa, returned a single tree under equal weighting. The monophyly of Scotaena was not recovered. Three new genera and five new species are described: Kaysara gen. nov., Pseudoscotaena gen. nov. and Pampathynnus gen. nov., Scotaena reversa sp. nov., Kaysara laterolata sp. nov., Kaysara apiciconcava sp. nov., Kaysara marginoplicata sp. nov. and Kaysara levicrenata sp. nov. Three species are transferred to other genera as follows: Eucyrtothynnus rosenbergi (Turner, 1910) comb. nov., Glottynoides genisei Kimsey, 1991 comb. nov., Ornepetes clypearis Durán-Moya, 1941 comb. nov. Scotaena now comprises four species: S. trifasciata Klug, 1810; S. horni (Turner, 1927); S. vetusta Turner, 1909; and S. reversa. An identification key and geographical distribution maps for the studied species are also provided.